An empirical antibiotic approach to couple infertility: Is it effective - Pasquale Scarano; Andrea Fabiani; Maria Pia Pavia; Giovanni Gison (Global Journal of Fertility and Research - Peertechz Publications, 2021)
Objective: To evaluate the benefit of antibiotic therapy (doxycycline, azithromycin and moxifloxacin) administered to couples with a history of infertility, suspected to suffer from an unrecognized Sexual Transmitted Disease (STI), that was not detected through standard laboratory exams. To evaluate the benefit of the treatment on the basis of improvement of seminal parameters and pregnancy, both natural and assisted. Patients and methods: The outpatient records of 350 infertile couples, were reviewed. Amongst them 136 couples met the study inclusion criteria such as history of infertility, no male or female infertility factors, negativity of laboratory cultural exams in both male and female partners, at least two seminal parameters suggestive for infections, and thus constituted the study sample. All couples were treated with 100 mg Doxycycline (1 tablet twice daily for 15 days a month for two months), 500 mg Azithromycin (1 tablet per day for 3 days every 10 days for 2 months), 400 mg Moxifloxacin (1 tablet per day for 7 days every month for 2 months). Couples were asked to refrain from having sex during the first month of therapy. Semen analyses were performed at the beginning and end of treatment. Statistical analyses comparing seminal parameters before and after treatment were carried out. Results: The mean age of male partners was 36,11 ± 7,03 (range 18-59), while female partners'mean age was 32,7 ± 6,33 (range 18-53). The mean duration of infertility was 3,26 ± 2,69 years. A history or current symptoms of STI was present in 27,9% of females and in 19,9 % of males, while in 11.8% of the sample both partners were symptomatic. In 10,3% of couples at least one miscarriage had occurred before initial evaluation. Before treatment, semen volume was normal in 86,8% and low in 10.3% hyperviscosity was recorded in 59,6% of cases, sperm fluidity was complete and incomplete in 91,2% and 8,8%, respectively. Leukocytospermia and agglutinations were found in 21,4% and 37,5% of subjects, respectively. The baseline sperm count was 17,3 ± 14,4 million/ml and 52,34 ± 52,88 million total, in mean. Asthenospermia was present in 69,1%. The rapid and slow motility were 11,9 ± 9,5 % and 12,1 ± 6,4% in mean, respectively. After antibiotic treatment, all parameters significantly improved compared to baseline figures (all p<0.05). In 27.2% of the sample full term pregnancies were reached in 27,2%. Pregnancies were reached after treatment in a mean time of 3,7 months. Conclusions: Couple infertility of suspected microbial etiology may be effectively treated with an antibiotic treatment regime based on a combination of doxycycline, azithromycin and moxifloxacin, which covers the most common STI pathogens. Following a holistic couple evaluation, this treatment strategy may increase the chance of natural pregnancy and decrease the need for invasive procedures.